Opioid-related emergency department visits and hospitalizations among patients with chronic gastrointestinal symptoms and disorders dually enrolled in the Department of Veterans Affairs and Medicare Part D. (7th September 2021) - Balbale, Salva N; Cao, Lishan; Trivedi, Itishree; Stulberg, Jonah J; Suda, Katie J; Gellad, Walid F; Evans, Charlesnika T; Jordan, Neil; Keefer, Laurie A; Lambert, Bruce L
Abstract: Purpose: We examined the prevalence of, and factors associated with, serious opioid-related adverse drug events (ORADEs) that led to an emergency department (ED) visit or hospitalization among patients with chronic gastrointestinal (GI) symptoms and disorders dually enrolled in the Department of Veterans Affairs (VA) and Medicare Part D. Methods: In this retrospective cohort study, we used linked national patient-level data (April 1, 2011, to October 31, 2014) from the VA and Centers for Medicare and Medicaid Services to identify serious ORADEs among dually enrolled veterans with a chronic GI symptom or disorder. Outcome measures included serious ORADEs, defined as an ED visit attributed to an ORADE or a hospitalization where the principal or secondary reason for admission involved an opioid. We used multiple logistic regression models to determine factors independently associated with a serious ORADE. Results: We identified 3, 430 veterans who had a chronic GI symptom or disorder; were dually enrolled in the VA and Medicare Part D; and had a serious ORADE that led to an ED visit, hospitalization, or both. The period prevalence of having a serious ORADE was 2.4% overall and 4.4% among veterans with chronic opioid use (≥90 consecutive days). Veterans with serious ORADEs were more likely to be less than 40 years old, male, white, and to have chronic abdominal pain, functional GI disorders, chronic pancreatitis, or Crohn's disease. They were also more likely to have used opioids chronically and at higher daily doses. Conclusion: There may be a considerable burden of serious ORADEs among patients with chronic GI symptoms and disorders. Future quality improvement efforts should target this vulnerable population.